A importância da prosódia na avaliação de qualidade e na compreensão e compreensibilidade da fala interpretada simultaneamente - Penha, Layla (2015)
This paper addresses the area of simultaneous interpretation, interpreting mode inserted in the field of Conference Interpreting. The purpose of this study is to verify the prosodic features of semi-spontaneous and interpreted speeches of a group of interpreters and analyze how such features may interfere in the assessment of quality and comprehension of the message delivered in interpretation. The subjects of this study were twelve female conference interpreters. The interpreters were recorded when producing a semi-spontaneous speech and during the simultaneous interpretation of a lecture. Three sampling segments representing the speech (extracted from the start, middle and end positions of the lecture) were selected. We conducted three types of assessment: an acoustic analysis of the selected speech samples, a perceptive assessment on the quality and comprehensibility of interpreters oral production, and an assessment on the quality of the content of the interpretation compared to the original lecture. Using the software Praat, we analyzed the prosodic features of interpreters semi-spontaneous and interpreted speeches acoustically, comparing them in terms of number and distribution of intonation groups and pauses; speech rate; and average, minimum and maximum fundamental frequency rates. By means of a questionnaire based on the Likert Scale applied to 90 judges, we assessed the impressive effects of interpreters oral production. Three interpreter trainers followed an assessment protocol to compare the speech produced by interpreters and the original lecture and verify completeness of original sense (S), errors (E) and omissions (O). Results were then compared for similarities and differences. This project was approved by the Brazilian Research Ethics Committee under no. 44465314.0.0000.5482